Navigating troubled waters: collaboration and resistance in state institutions in Nazi-occupied Norway. Issue 1 (1st January 2021) - Hetland, Ø.; Karcher, N.; Simonsen, K. B.
ABSTRACT: This article examines and compares the patterns of collaboration and resistance in the school sector, the police, and the ministerial bureaucracy, which experienced very different developments during the German occupation of Norway. While teachers created a powerful resistance movement, the police became a useful tool for the occupier. The development within the ministerial bureaucracy was highly differentiated, where some departments were permeated by a new, National Socialist ethos, and others characterized by a culture of collective resistance. Three main factors led to the disparate responses: the framework established by the German authorities, and their varying interests in different spheres; the internal values, role perceptions, and political views within the three groups; and the social dynamics within given sectors. Leaders' views and influence, the pace and intensity of Nazification, and the ability to mobilize quickly and collectively, were of decisive importance.